Pengaruh Penggunaan Metode Evaluasi Kinerja Dan Target Terhadap Produktivitas Karyawan Pada PT. Andika Mandiri Perkasa - Cahyani, Andini Ayu; Nersiwad; Kasnowo (PT. Kreasi Karya Majakata, 2024)
This research aims to analyze the effect of using performance evaluation methods and targets on employee productivity at PT Andika Mandiri Perkasa. Performance evaluation methods and target setting are two important components in human resource management that can affect the level of organizational productivity. This research uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to employees of PT Andika Mandiri Perkasa. The results showed that there is a significant relationship between performance evaluation methods and increased employee productivity. Evaluations that are conducted objectively and transparently are able to provide constructive feedback, so that employees can improve and increase their performance. In addition, setting clear and measurable targets also has a positive effect on employee productivity, because specific targets provide clear direction and motivate employees to achieve better results. Overall, this study concludes that the use of effective performance evaluation methods and realistic target setting can improve employee productivity at PT Andika Mandiri Perkasa. The implementation of this strategy is expected to be a reference for companies in developing more effective human resource management policies.